MEDIA EFFECTS ON VOTING BEHAVIOR - Nasser N. Alotaibi (European Scientific Journal, ESJ, 2013)
This is a review study investigating the effects of the media on voting behavior. We reviewed the cited literature. The present study showed that the role of the media in influencing election results is generally quite small. However, this insignificance is not inherent; it cannot be attributed to out-dated class rationalisation or even to “resurgent” economic factors. Rather, it is the result of other competing factors including: the counteracting factor, which is a reference to the constant battles between rival candidates. Naturally, positive, image-conscious campaigning by candidates is mirrored by all sides; therefore, on a neutral individual no overall influence would be visible. Another factor involves the absence of clear superiority, which refers to the rare occasion in which one candidate (or party) clearly excels in its media campaign, while its opponents do not use the media in an effective manner. This superiority occurs rarely because all politicians employ PR and media consultants.